Neural Mechanisms of Anaphoric Reference Revealed by fMRI - Hammer, Anke; Jansma, Bernadette; Tempelmann, Claus; Münte, Thomas F. (Frontiers in Psychology, 2011)
Pronouns are bound to their antecedents by matching syntactic and semantic information. The aim of this functional magnetic resonance (fMRI) study was to localize syntactic and semantic information retrieval and integration during pronoun resolution. Especially we investigated their possible interaction with verbal working memory manipulated by distance between antecedent and pronoun. We disentangled biological and syntactic gender information using German sentences about persons (biological/syntactic gender) or things (syntactic gender) followed by congruent or incongruent pronouns. Increasing the distance between pronoun and antecedent resulted in a short and a long distance condition. Analysis revealed a language related network including inferior frontal regions bilaterally (integration), left anterior and posterior temporal regions (lexico-semantics and syntactic retrieval) and the anterior cingulate gyrus (conflict resolution) involved in pronoun resolution. Activities within the inferior frontal region were driven by Congruency (incongruent > congruent) and Distance (long > short). Temporal regions were sensitive to Distance and Congruency (but solely within long distant conditions). Furthermore, anterior temporal regions were sensitive to the antecedent type with an increased activity for person-pronouns compared to thing-pronouns. We suggest that activity modulations within these areas reflect the integration process of an appropriate antecedent which depends on the type of information that has to be retrieved (lexico-syntactic posterior-temporal, lexico-semantics anterior-temporal). It also depends on the overall syntactic and semantic complexity of long distant sentences. The results are interpreted in the context of the Memory-Unification-Control model for sentence comprehension as proposed by Vosse and van Kempen (2000), Hagoort (2005), and Snijders et al. (2009).